Use of Tik Tok Apps in Early Childhood and Parental - Katrin, Herlyn Jenn; Chusairi, Achmad (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
The purpose of this study is to describe the use of tik tok application in early childhood and the parental control given to children who use tik tok. This study has five subjects interviewed, namely mothers using qualitative methods, specifically phenomenological studies. Based on the purpose of the interview and the results of the analysis, it can be concluded that children's activities in using tik tok are fairly intense and spend a long time so that they have an effect on addiction. Tik tok besides having a positive effect on children which is useful in increasing the mood of learning and creativity, but there are also negative influences, namely adult videos and addiction which have an impact on the development of children's personalities. Because parental control is not firm in limiting children's use of tik tok, it can be seen from children who can still explore the application without the knowledge of parents. Parents' prohibitions are not accompanied by education that provides understanding to children about the benefits of tik tok which is only used to complement the needs in the learning process so that limiting and supervising is not enough to minimize the use of tik tok in children.Keyword: Tik Tok App, Early Childhood, Parental Control